The impact of Quick Service Restaurant Brand Extension Evaluations on Purchase Intention and eWOM - Desmond Edbert Hartono; Michael Kyrieko; Fathony Rahman; Bernardinus Yudianto (Universitas Prasetiya Mulya, 2021)
Brand extension has been popularly used in the marketing field. It is because, when a firm extends their brand, they have a purpose to introduce their new brand/product without any challenge by connecting with the parent brand. Thus, between the parent brand and extension brand are not apart from association and similarity. Brand image has a part in the ability of consumers to make association to the parent brand and its extension. So, brand image and extension similarity is considered to be important when evaluating brand extension. Brand extension evaluation also will affect consumers’ purchase intention. In this study, the effect of eWOM through social media was also tested to the brand extension evaluation. In this research we use Starbucks and Starbucks Reserve as an object of the study with a within subject experiment. The first study was done using 2x2 (Brand image fit: Utilitarian/Symbolic, Brand extension similarity: High Similarity/Low Similarity), tested the effect of purchase intention and the second study was 2x2 (Brand image fit: Utilitarian/Symbolic, Brand extension similarity: High Similarity/Low Similarity) to measure the effect of eWOM. The findings in the first study shows the positive effect of purchase intention on extension similarity. If brand extension similarity and brand image are combined there will be interaction. The second study only shows the main effect, both on image and similarity. In the second study there is no interaction.